Influence of NiTi alloy on the root canal shaping capabilities of the ProTaper Universal and ProTaper Gold rotary instrument systems - DUQUE, Jussaro Alves; VIVAN, Rodrigo Ricci; CAVENAGO, Bruno Cavalini; AMOROSO-SILVA, Pablo Andrés; BERNARDES, Ricardo Affonso; VASCONCELOS, Bruno Carvalho de; DUARTE, Marco Antonio Hungaro (Journal of Applied Oral Science, 2017)
Objective This study aimed to evaluate the influence of the NiTi wire in Conventional NiTi (ProTaper Universal PTU) and Controlled Memory NiTi (ProTaper Gold PTG) instrument systems on the quality of root canal preparation. Material and Methods Twelve mandibular molars with separate mesial canals were scanned using a high-definition microcomputed tomography system. The PTU and PTG instruments were used to shape twelve mesial canals each. The canals were scanned after preparation with F2 and F3 instruments of the PTU and PTG systems. The analyzed parameters included the remaining dentin thickness at the apical and cervical levels, root canal volume and untouched canal walls. Data was analyzed for statistical significance by the Friedman and Dunn’s tests. For the comparison of data between groups, the Mann-Whitney test was used. Results In the pre-operative analysis, there were no statistically significant differences between the groups in terms of the area and volume of root canals (P>;.05). There was also no statistically significant difference between the systems with respect to root canal volume after use of the F2 and F3 instruments. There was no statistical difference in the dentin thickness at the first apical level between, before and after instrumentation for both systems. At the 3 cervical levels, the PTG maintained centralization of the preparation on the transition between the F2 and F3 instruments, which did not occur with the PTU. Conclusion The Conventional NiTi (PTU) and Controlled Memory NiTi (PTG) instruments displayed comparable capabilities for shaping the straight mesial root canals of mandibular molars, although the PTG was better than the PTU at maintaining the centralization of the shape in the cervical portion.